Getting the ball rolling: an exploration of the drivers and barriers towards the implementation of bottom-up circular economy initiatives in Amsterdam and Rotterdam - Russell, Max; Gianoli, Alberto; Grafakos, Stelios (Journal of environmental planning and management, 2020)
The notion of Circular Economy is often presented as a more sustainable alternative to a 'linear' economic system. However, there is a distinct gap in the academic literature surrounding the concept, particularly in terms of implementation. This article provides an initial exploration into critical factors influencing the process of implementation by studying 12 bottom-up CE initiatives in the two Dutch cities of Amsterdam and Rotterdam. In-depth semi-structured interviews were conducted with key stakeholder(s) for each initiative in order to identify the perceived importance of the critical factors. In total, 18 critical factors were identified, grouped into 5 overarching categories: financial, institutional, policy and regulatory, technology and knowledge, and social. The analysis shows that the critical factors identified do not act in isolation, and form a complex web of interconnecting critical factors. Furthermore, it illustrates how certain critical factors are of significant influence at particular stages throughout the process of implementation.